Increasing efficiency of a 33 MW OTEC in Indonesia using flat-plate solar collector for the seawater heater - Setiawan, Iwan Rohman; Purnama, Irwan; Halim, Abdul (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2017)
This paper presents a design concept of Ocean Thermal Energy Conversion (OTEC) plant built in Mamuju, West Sulawesi, with 33 MWe and 7.1% of the power capacity and efficiency, respectively. The generated electrical power and the efficiency of OTEC plant are enhanced by a simulation of a number of derived formulas. Enhancement of efficiency is performed by increasing the temperature of the warm seawater toward the evaporator from 26ËšC up to 33.5ËšC using a flat-plate solar collector. The simulation results show that by increasing these a water temperature up to 33.5ËšC, the generated power will increase up to 144.155 MWe with the OTEC efficiency up to 9.54%, respectively. The required area of flat-plate solar collector to achieve the results is around 6.023 x 106 m2.